(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Purpose. To develop anti-infective peptide (AIP) LL37sustained delivery system that can be used for ocular infections treatment. Methods. AIPLL37(cathelicidin) was encapsulated in different particles (alginate, chitosan, silica) under magnetic stirring. Encapsulation efficacy (EE) and LL37 release from particles was checked using the ELISA method. The particle morphology was studied by transmission electron or light microscopy. Cytotoxicity of particles with encapsulated LL37was assessed using WST-1 based colorimetric assay. Results. EE of LL37in the alginate microparticles (AMPs) was 13.8 %. AMP size was 15—20 um. EE of LL37in silica nanoparticles (SiNPs) was 54.4 %. SNPsize was 10—20 nm. Sustained release of LL37in AMPs occurred up to the 7th day and in SNP’s — up to the 21st day. No LL37 release occurred from chitosan particles. WST-1 based colorimetric assay showed no increased cytotoxicity regarding human corneal epithelial cells of particles with encapsulated LL37compared to control clear particles. Conclusion. For the first time micro - and nanoparticle based AIP LL37 sustaineddelivery system was developed. Sustained release of LL37 from AMPs and SiNPs was proved. No cell toxicity was found. SiNP encapsulated LL37showed better EE and longer release of AIP compared to AMP encapsulated LL37.